Sikap Jamaah Masjid Terhadap Tradisi Puji-Pujian Sebelum Sholat Studi Kasus Jamaah Masjid di Desa Giling dan Kelurahan Sumurboto - Nur Fauzan Ahmad (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2017)
Puji-pujian is the recitation of solawat, dhikr and prayer coupled with Javanese sair-sair sung to await the arrival of praying in congregation at mosque or langgar. This paper discusses the waning of the tradition of praise in society. The research was conducted in Desa Giling, Sub-district Pabelan, Semarang Regency and Kelurahan Sumurboto, Banyumanik Sub-District, Semarang City. The existence of this tradition began to fade due to the entry and development of movements that seek to purify Islam. The party that supports this tradition is from NU culture. They consider this practice good because it has a basis, and has many benefits da'wah. Who refuses to regard praise as an unclear practice of guidance and potentially disturbing the congregation of other worshipers.